Copies of the everyday : advertisements in Republican China, 1911-37, and the writing of everyday history - Ho, Josiah Chit Ian (Nanyang Technological University, 2021)
Advertisements have always been around us. Located traditionally and most commonly in the print medium, the proliferation of newspapers and other print material in the late nineteenth and early twentieth century saw a similar proliferation of advertisements. In Republican China, advertisements were a ubiquitous part of the lives of both the elite as well as the common people. As such, one can think of advertisements as a space where both the ordinary and the elite had shared a common interaction. I refer to this space as the everyday. In doing so, this thesis also calls for a rethinking of what everyday conventionally means – which is usually used interchangeably with the quotidian, or the ordinary – as a term which accounts for both the ordinary as well as the elite. I contend that advertisements are an often under-utilized yet useful source in telling a history of the everyday. Existing work on advertisements in Republican China have often focused either on individual commodities or have used advertisements as a supplementary source for other histories. A broader history of advertisements in Republican China is lacking in the current academic conversation, and this thesis intends to fill that gap. This thesis has two key aims: the first, to write an everyday history of Republican through the use of advertisements. Through the study of print advertisements in three different commodity categories: everyday items, patent medicines, and cigarettes, I aim to tell a history of the everyday experience in Republican China. The analysis of the advertisements from the respective commodity categories gets increasingly microscopic, where we first examine the general consumer culture surrounding everyday items; following that we examine one resulting strand of this everyday narrative which involves national consciousness; finally from the national consciousness, we look at how local-foreign binaries are played out in these advertisements. The second goal is more historiographic in nature which is to demonstrate the importance of writing an everyday history within the context of historiography and consider the implications of an everyday approach in the writing of history. I contend that when one accounts for this everyday in historiography, we can move away from a linear ‘top-down’ or ‘bottom-up’ approach and consider instead how a more inclusive history is instead flattened.